Effect of mechanical soil management through subsoiling and preparatory tillage on growth and nutrients uptake of sugarcane (Saccharum complex hybrid) plant and ratoon crop - KUMAR, SATENDRA; SAINI, S K; BHATNAGAR, AMIT; THAKUR, T C (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 2008-2010 at G B Pant University of Agriculture and Technology, Pantnagar to study the response of sugarcane plant and ratoon crops to subsoiling and preparatory tillage. The experiment consisting of five subsoiling treatments in plant crop (No subsoiling, subsoiling at 1.0 m, subsoiling at 1.5 m, cross- subsoiling at 1.0 m and cross-subsoiling at 1.5 m distance) and three preparatory tillage practices (two harrowing, four harrowing and one rotavator) was laid out in strip plot design with three replications. The ratoon crop was managed mechanically with a newly developed Sugarcane Ratoon Manager in all the subsoiling treatments. The root and shoot growth, nutrients uptake, and yield of plant and ratoon crops increased with the intensity of subsoiling. The most intense subsoiling, i.e. cross-subsoiling at 1.0 m in plant crop resulted significantly more root biomass (70.1 g/ m3), shoot dry matter (40.9 tonnes/ha), nutrient uptake (220.9 kg N, 26.6 kg P and 307.6 kg K/ha), cane weight (883.8 g), millable canes (100.2 thousand/ha) and cane yield (75.8 tonnes/ha). Subsoiling practices coupled with mechanized management of ratoon exhibited significant improvement in root biomass (73.6 %), shoot dry matter (31.7 %), NPK uptake (29.3, 34.9 and 34.3 %, respectively), cane weight (13.6%), millable canes (21.9%) and cane yield (26.6%) over manual operations (control). All the preparatory tillage practices were at par with respect to the parameters studied, however, root biomass increased significantly with increase in number of tillage practices being maximum in four harrowing treatment.